An investigation on hydrogen storage thermodynamics and kinetics of Nd–Mg–Ni-based alloys synthesized by mechanical milling. (27th July 2016) - Zhang, Yanghuan; Li, Baowei; Ren, Huiping; Yuan, Zeming; Yang, Tai; Qi, Yan
Abstract: In order to improve the hydrogen storage kinetics of NdMg12 -type alloy, the Mg in the alloy was partially substituted by Ni, and mechanical milling technology was used to fabricate the nanocrystalline and amorphous NdMg11 Ni +  x wt.% Ni ( x  = 100, 200) alloys. Effects of Ni content and milling time on the gaseous hydrogen storage thermodynamics and kinetics of alloys were investigated systematically. The structures of as-cast and milled alloys were characterized by X-ray powder diffraction (XRD), scanning electron microscopy (SEM) and high-resolution transmission electron microscope (HRTEM). The pressure-composition isotherms ( P-C-T ) and the hydrogen absorption and desorption kinetics of the as-milled alloys were measured by an automatically controlled Sievert's apparatus and a differential scanning calorimetry (DSC) (SDT-Q600) with a H2 detector. Thermodynamic parameters (Δ H and Δ S ) for the hydrogen absorption and desorption of alloys were calculated from Van't Hoff equation. Hydrogen desorption activation energy of alloy hydride was also estimated by using Arrhenius and Kissinger methods. It is found that the variation of Ni content brings on a slight effect on the thermodynamic properties of the alloys, but it significantly improves the hydrogen absorption and desorption kinetics. The improved gaseous hydrogen storage kinetics of alloys are considered to be ascribed to a decrease in hydrogen desorption activation energy caused by increasing Ni content and prolonging milling time. Highlights: Nd-Mg-Ni-based NdMg12 -type alloys were synthesized by ball milling. Structures of as-milled alloys were characterized by SEM, XRD and TEM. Effect of milling time and Ni content on thermodynamics were investigated. Gaseous hydrogen absorption and desorption kinetics was investigated. Activation energy was calculated by Arrhenius and Kissinger methods.